A validade da cláusula de não concorrência inserida no contrato de emprego brasileiro - Baraldi, Cristiane (2015)
The doctrine and jurisprudence thoroughly discuss the insertion possibility of the non-competition clause into Brazilian employment contracts and, if implemented, which would be the necessary requirements for the validity of this type of clause. The non-competition clause, also known as quarantine, has the purpose of averting that an employee whom has exerted activities that provide company’s strategic or confidential knowledge practice, on their own or for others, competitive activity after the employment contract’s termination. It happens that this type of clause puts in conflict two fundamental rights: the work freedom of an employee and the employer’s property rights. The Brazilian law is silent about the insertion of these types of clauses in the labor acts, leaving to the doctrine and jurisprudence a search for a better solution to this conflict through: the hermeneutic rules, collision among fundamental rights, from the Brazilian law general norms and the systematic and teleological analysis of the national laws. Moreover, many other constitutional guarantees are involved in this conflict. Together with the employer’s property rights, subjoins the guaranteed: free enterprise, free competition and the private property itself. In another hand, to the employee’s freedom of work the following guarantees are aggregated: the labor social value, labor as the social right capable of providing dignified existence, the appreciation of human labor and the search for plenary employment. Currently the doctrine and majority jurisprudence have solved this problematic based upon: absence of express legal prohibition in the Brazilian law regarding the pact of this type of clause, in the proportionality principle, in post contractual responsibility and comparative law. Thereby, it would be possible to insert the non-competition clause in a labor contract, but only if observed a series of requirements, specially: not precluding the employee of working, but only to exert determined activities that imply in competition to the company and risks of financial loss; limit the geographical area in which the employee will be restricted and the length of this limitation; previse a compensatory indemnity payment to the employee reasonable and adequate to the imposed restrictions; and, attend to social interest